Redéfinitions de la maternité et migrations. Le cas des épouses de migrants à Mexico - Anna Perraudin (Les Cahiers ALHIM)
Unlike other studies of ‘distance maternity’ in transnational families, this article will examine the situation of mothers who stay with their children in the absence of their partners involved in long-distance migration. It seeks to understand how the experience of being a mother is transformed by reviewing various dimensions: models of maternity, practices, representations of self. It focuses on Mexican families living in working class neighbourhoods in order to analyze the impact in urban areas. Based on an ethnographic study carried out in Mexico with indigenous families, the article highlights several factors in the shifting parental roles within the couple and the family: intergenerational conflicts relating to the definition of norms of maternity, involvement of individuals in ethnic social relationships, geographic dispersal of the family and diversity of characteristic areas of socialization in the city.